Simulations of the L-H transition dynamics with different heat and particle sources - 李会东 王占辉 Jan Weiland 冯灏 孙卫国 (Chinese physics B, 2015)
It is crucial to increase the total stored energy by realizing the transition from a low confinement （L-mode） state to a high confinement （H-mode） state in magnetic confinement fusion. The L-H transition process is simulated by using the predictive transport code based on Weiland＇s fluid model. Based on the equilibrium parameters obtained from equilibrium fitting （EFIT） in the experiment, the electron density ne, electron temperature Te, ion temperatures lq, ion poloidal Vp, and toroidal momenta Vt are simulated self-consistently. The L-H transition dynamic behaviors with the formation of the transport barriers of ion and electron temperatures, the electron density, and the ion toroidal momenta are analyzed. During the L-H transition, the strong poloidal flow shear in the edge transport barrier region is observed. The crashes of the electron and ion temperature pedestals are also observed during the L-H transition. The effects of the heating and particle sources on the L-H transition process are studied systematically, and the critical power threshold of the L-H transition is also found.